The Porch and its Interaction with Building Design in Arid Zones - Berghout, Belkacem; Berghout, Walid; Berghout, Imene (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Improving the energy performance of buildings has thus become a major challenge, as the building sector is now one of the main sources of energy consumption and one of the main contributors to greenhouse gas emissions. Faced with these alarming challenges, current building design in the north is based on minimizing heat loss. However, this logic is not necessarily the most relevant in southern countries, characterized by excessive heat and insufficient, variable rainfall.
Keywords: arid zones; Biskra; design processes; energy performance; porch